Unveiling the associations between conscientiousness and emotional intelligence in Paralympic athletes - Sarikabak, Murat; Ayranci, Mert; Yalcin, Ilimdar; Talaghir, Laurentiu-Gabriel; Bentea, Cristina-Corina (Frontiers in Psychology, 2024)
This study investigates the association between conscientiousness and emotional intelligence (EI) in Paralympic athletes. A sample of 274 athletes (190 male, 84 female) was analyzed using the Schutte EI Scale and a Conscientiousness scale from the Big Five Personality Traits. Results indicated a significant positive relationship between EI and conscientiousness, with EI explaining 28% of the variance in conscientiousness (p < 0.05). Specifically, optimism and mood regulation demonstrated a high positive correlation with conscientiousness (r = 0.501), while assessing feelings showed a moderate positive correlation (r = 0.391), and using feelings revealed a low positive correlation (r = 0.120). Gender-based analysis revealed that female athletes scored significantly higher in emotional usage. These findings suggest that promoting EI in Paralympic athletes could enhance conscientiousness, potentially benefiting their resilience and psychological stability. Future research should explore longitudinal designs to examine these associations further.